'I could have been the caretaker in a suit': men as primary school SENCos in an era of change. Issue 7 (2nd October 2020) - Pulsford, Mark
ABSTRACT: This paper examines the experiences of four men working as Special Educational Needs Coordinators in primary schools in England. There is currently no published research that draws insights from the small population of male SENCos, nor that explores the gendered aspects of leading for inclusion. Set against recent SEN policy reform and a changing demographic profile of the SENCo population, the paper contributes novel understandings of men's experiences of SEN coordination and middle leadership, as ascertained through narrative interviews. By interrogating these previously unheard stories and drawing on the theory of 'practice architectures', recommendations for policy and practice in the training and induction of new SENCos are made.